PENGETAHUAN DAN USIA MENIKAH PERTAMA DENGAN DETEKSI DINI KANKER SERVIKS - Dolang, Mariene (STIKES Pasapua Ambon, 2020)
Introduction : Reproductive Health is a state of complete physical, mental and social well-being that is not solely free from diseases related to the reproductive system. Cervical cancer is cancer that grows from cervical cells, cervical cancer can originate from cells in the cervix but can also grow from cervical cells. This situation is usually accompanied by bleeding and abnormal vaginal discharge. The purpose of this study was to analyze the relationship between age at first marriage and the role of health workers with early detection of cervical cancer in women of childbearing age. Method : The design of this study was an observational analytic study with a cross sectional approach, to analyze the relationship between the age of first marriage and the role of health workers with early detection of cervical cancer in Benteng health centers. The population is all WUS aged 15-49 years who are in the area of Benteng Health Center, amounting to 200 respondents. Resulth : The results of this study use the Chi Square test, it is known that there is a relationship between knowledge (p = 0.004) and first marriage (p = 0.014) with early detection of cervical cancer. Conclusion : the relationship between knowledge and age of first marriage with early detection of cervical cancer in WUS at Benteng Health Center It is recommended for married WUS to always pay attention to their reproductive health by examining early detection of cervical cancer. The fort health center is more active in providing information to the public, especially to mothers about the early detection of cervical cancer as an effort to prevent and prevent cervical cancer.